2016
DOI: 10.1016/j.neuroscience.2015.12.046
|View full text |Cite
|
Sign up to set email alerts
|

White matter apoptosis is increased by delayed hypothermia and rewarming in a neonatal piglet model of hypoxic ischemic encephalopathy

Abstract: Therapeutic hypothermia is widely used to treat neonatal hypoxic ischemic (HI) brain injuries. However, potentially deleterious effects of delaying the induction of hypothermia and of rewarming on white matter injury remain unclear. We used a piglet model of HI to assess the effects of delayed hypothermia and rewarming on white matter apoptosis. Piglets underwent HI injury or sham surgery followed by normothermic or hypothermic recovery at 2 h. Hypothermic groups were divided into those with no rewarming, slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 37 publications
3
72
0
1
Order By: Relevance
“…Гипотермия (переохлаждение) снижает образо-вание свободных радикалов и уровень глутамата, умень-шает потребность в кислороде и уменьшает апоптоз [4,78,79]; одним из ведущих механизмов терапевтиче-ского эффекта считается противовоспалительный [80]. Основные эффекты гипотермии направлены на действие в период «окна возможностей», или латентного пери-ода энергетической недостаточности [6], который, как говорилось выше, предположительно длится с 30 мин после рождения до 24-48 ч. Именно в этот период появляется возможность не допустить или минимизиро-вать вторичную фазу энергетической недостаточности.…”
Section: обзор литературыunclassified
“…Гипотермия (переохлаждение) снижает образо-вание свободных радикалов и уровень глутамата, умень-шает потребность в кислороде и уменьшает апоптоз [4,78,79]; одним из ведущих механизмов терапевтиче-ского эффекта считается противовоспалительный [80]. Основные эффекты гипотермии направлены на действие в период «окна возможностей», или латентного пери-ода энергетической недостаточности [6], который, как говорилось выше, предположительно длится с 30 мин после рождения до 24-48 ч. Именно в этот период появляется возможность не допустить или минимизиро-вать вторичную фазу энергетической недостаточности.…”
Section: обзор литературыunclassified
“…[1] However, approximately half of survivors have persistent neurodevelopmental disabilities despite receiving hypothermia. [1, 2] We theorize that adverse effects from delaying the induction of hypothermia [3] and rewarming [4, 5] may be partially responsible for these neurologic impairments. We previously demonstrated that rewarming increases cortical neuronal apoptosis and caspase-3 cleavage after hypoxia-ischemia (HI) in a piglet model.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Hypothermia and rewarming also promote glial apoptosis in the white matter, an effect that may be independent of HI in some brain regions. [5] Cortical and white matter injuries on MRI predict neurodevelopmental and motor impairments in survivors of HIE. [6, 7] Thus, there is need to define the mechanisms through which apoptotic cascades are activated after HI, hypothermia, and rewarming; to clarify targets for adjuvant therapies; and to minimize off-target effects from hypothermia and rewarming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain injury biomarkers, such as circulating blood-based analytes (14,15) or physiologic measures of autonomic dysfunction (16,17), might be able to identify neonates at greatest risk of severe brain injury and provide real-time feedback on treatment efficacy. Optimizing cerebrovascular blood pressure autoregulation (18)(19)(20) with individualized hemodynamic goals and avoiding hypocapnia (21) might also improve outcomes. Moreover, current intrapartum fetal monitoring techniques do not sufficiently identify babies at risk of intrapartum hypoxia.…”
mentioning
confidence: 99%